Is there still a role for fetal and perinatal post-mortem radiography?. Issue 1 (March 2015) - Arthurs, O.J.; Calder, A.D.; Klein, W.M.
Abstract The fetal and perinatal autopsy has incorporated imaging for many years, usually skeletal radiographs, which can be diagnostically useful in the post-mortem setting. In fetal or perinatal post-mortem skeletal surveys (PMSSs or "babygrams"), usually two whole-body radiographs are performed for the assessment of bone biometry, gestation estimation and congenital skeletal abnormalities. We outline the clinical settings and acquisition techniques involved, with particular emphasis on diagnostic yield and costs involved. We briefly discuss the alternative radiology modalities (CT and MRI scan). We conclude that there is no longer a diagnostic or cost-effective base for routine fetal and perinatal radiography and a targeted approach based upon the clinical history may now be more pragmatic.